FAKTOR-FAKTOR YANG MENENTUKAN KEPUASAN PELANGGAN SEPEDA MOTOR MATIC HONDA DI KOTA DENPASAR - PUTRI, NI KADEK LESTARI; ASIH, NI MADE; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 4 No 1 (2015)DO - 10.24843/MTK.2015.v04.i01.p080, 2015)
This study aimed to elaborate the dominant factor affecting consumer’s loyalties regarding Honda motor matic and to determine effective marketing strategy for this product.  This study conducted at Denpasar where 150 respondents randomly chosen as the data sources.  From factor analysis, we found emotional factor is the most dominant factor for consumer’s loyalties with eigen value as much as 3,365 and variance explained by this factor is 48,08 percent.  Meanwhile, to determine effective marketing strategy, we found the product’s quality dominated by its design; service quality dominated by service reliability, emotional factor dominated by the product’s esthetic, each of these has communalities as much as 56,38 percent; 72,33 percent, and 65,20 percent respectively.
Keywords: Dominant factor, Factor analysis, Honda motor matic, Marketing strategy